Management of alveolar defect with one-piece implant and index of gingival porcelain shade selection in a North Indian Youth - Devendra Chopra; Vipin Bhatnagar; Sudhanshu Srivastava (Wolters Kluwer Medknow Publications, 2018)
Esthetics is a prime demand for patients who seek anterior replacement of missing teeth. Resorption of the alveolar bone of the edentulous area occurs if left untreated for a long time. It further leads to thinning of the labial cortical plate in the maxillary arch. Few other reasons for narrowing of the alveolar crest are anatomic such as congenitally missing teeth and pathologic, that is dental trauma from tooth avulsion. Nowadays, patients always look for a fixed alternative for the restoration of missing teeth. Other than a conventional fixed partial denture, dental implants are the first choice of treatment. It is one of the difficult tasks for the clinician as well as the dental technician to meet the expectation of the patient when the ridge defect is present in the edentulous area. Extensively invasive procedures such as guided bone regeneration for correction of alveolar defects lead to prolong treatment time and induce psychological trauma to the patient.